1977
DOI: 10.1007/bf01868148
|View full text |Cite
|
Sign up to set email alerts
|

Proton transport by bacteriorhodopsin through an interface film

Abstract: Interface films of purple membrane and lipid containing spectroscopically intact and oriented bacteriorhodopsin have been used as a model system to study the function of this protein. Small positive charges in surface potential (less than 1 mV) are detected upon illumination of these films at the air-water interface. These photopotentials are not affected by overlaying the interface film with a thin layer (0.3 mm) of decane. However, they are dramatically increased when lipid soluble proton carriers FCCP or DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The 5-to 10-nm red shift of the action spectrum with respect to the absorption spectrum is within the bandwidth of the interference filters used; however, the shift may also reflect contributions from the excitation of red-shifted intermediates in the photocycle. Very similar action spectra have been reported for purple membrane based on the wavelength dependence of tAbsorption spectra were recorded in 1% DMPC/1% CHAPS/0.2% SDS in 10 mM phosphate buffer at pH 6. photovoltages in oriented films (11,12). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The 5-to 10-nm red shift of the action spectrum with respect to the absorption spectrum is within the bandwidth of the interference filters used; however, the shift may also reflect contributions from the excitation of red-shifted intermediates in the photocycle. Very similar action spectra have been reported for purple membrane based on the wavelength dependence of tAbsorption spectra were recorded in 1% DMPC/1% CHAPS/0.2% SDS in 10 mM phosphate buffer at pH 6. photovoltages in oriented films (11,12). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of the steady-state current to the peak current (n-decane) is increased by a factor of 100-1000 compared with the sandwich-like structure (9). It should be noted that the dark current is 10 as in a except that n-hexadecane was used instead of n-decane. experiment showed that the sign of the photocurrent seems to be distributed randomly.…”
Section: Methodsmentioning
confidence: 99%
“…Other methods for studying the photoelectric effect of bacteriorhodopsin have been reported. Purple membrane was transferred to an air/water or oil/water interface (10). Another approach consisted of combining purple membrane vesicles with lipid impregnated membrane filters (11,12).…”
mentioning
confidence: 99%
“…The method is based on the concept of spreading, not the isolated protein, but rather a mixture of purple membrane fragments and lipid. We present here an analysis of the physical and spectroscopic properties of these interface films and, in the following paper (Hwang, Korenbrot & Stoeckenius, 1977), a study of the function of bacteriorhodopsin in the films.…”
mentioning
confidence: 99%